Laser Light Trapping Phenomenon in a 3D Radiotherapy Polymer Gel Dosimeter - Kozicki, Marek (Materials (Basel), 2021)
This paper aims to explain the phenomenon of laser light trapping (LLT) in a 3D polymer gel dosimeter. A VIC-T polymer gel dosimeter containing 17% N-vinylpyrrolidone, 8% N,N′-methylenebisacrylamide, 12% tert-butyl alcohol, 5% gelatine, 0.02% hydroquinone and 14 mM tetrakis(hydroxymethyl)phosphonium chloride was used in this study. It was exposed to green laser light with a wavelength of 532 nm. A film was recorded during the exposure. After exposure, Raman spectroscopy was used to study the reactions taking place inside the dosimeter. The obtained results were used to explain what the LLT phenomenon is, what are the consequences for the dosimeter in which such a phenomenon occurs, and what dosimeter components play an important role in the occurrence of LLT. In addition, the conditions under which 3D polymer gel dosimeters can be measured using optical computed tomography at short wavelengths of visible laser light are indicated.